Essays in empirical industrial organization - Wu, Chi-Yin (Jenny) (Kansas State University, 2012)
This dissertation is composed of two essays in the field of Industrial Organization. Specifically, the empirical studies are conducted by focusing on the market structure and competition issues in the airline industry. The first essay investigates entry deterrence through incumbents’ pricing strategies in the airline industry. Recent research finds evidence that incumbent airlines tend to cut fares in response to the “threat” of entry by Southwest Airlines. Instead of focusing on the entry threat by a single carrier, this essay re-examines this issue by looking at incumbent airlines’ price response when entry is threatened by a wider variety of potential entrant airlines. Results show that incumbents’ response vary by the identity of the firm making the threat. As expected, incumbents cut fares in response to the threat of entry by some potential entrants; however, a new result is also found that incumbents may respond by raising their fare depending on who is making the threat. The second essay looks into an antitrust-relevant issue in the airline industry. Proper antitrust analysis often focuses on whether the concerned differentiated products are truly competing with each other. This essay uses a structural econometric model to investigate whether nonstop and connecting air travel products effectively compete with each other. Estimate results suggest that connecting products may be an attractive alternative to nonstop products for leisure travelers but less so for business travelers. If connecting products are counterfactually eliminated, the empirical model predicts small price changes for nonstop products. This suggests that the two product types only weakly compete with each other and can be treated as being in separate product markets for antitrust purposes.
Keywords: Airline competition; Empirical entry model; Market segmentation; Discrete choice demand model; Relevant product markets; Economics (0501)